VIABILITAS DAN VIGOR BENIH PADA JENIS MEDIA TANAM HIDROTON, COCOPEAT, ROCKWOOL, MOSS, DAN HIDROGEL - Khotimah, Khusnul; Roni; Waraningtyas, Indira; Nissa, Ismatun (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Seed germination is the early stage that determines the success of plant growth, so choosing the right planting medium is very important. This study aims to determine the germination rate of lettuce (Lactuca sativa L.) seeds in various types of planting media and compare the effectiveness of these media in supporting the germination process. This study used a Completely Randomized Design (CRD) with one factor, namely the type of planting media consisting of hydroton (P1), cocopeat (P2), rockwool (P3), moss (P4), and hydrogel (P5), each with three replications. Observations included seed germination, number of leaves and plant height. Data were analyzed using the Kruskal–Wallis nonparametric test because the data were not normally distributed. The results of the study showed that in the viability and vigor testing of seeds, rockwool germination media provided the best results as indicated by a germination rate of 100%, a vigor index of 93.3% and a growth simultaneity of 96.7%.